2014
DOI: 10.3133/ofr20141030
|View full text |Cite
|
Sign up to set email alerts
|

2013 update on sea otter studies to assess recovery from the 1989 <i>Exxon Valdez</i> oil spill, Prince William Sound, Alaska

Abstract: For more information on the USGS-the Federal source for science about the Earth, its natural and living resources, natural hazards, and the environment-visit http://www.usgs.gov or call 1-888-ASK-USGS For an overview of USGS information products, including maps, imagery, and publications, visit http://www.usgs.gov/pubprodTo order this and other USGS information products, visit http://store.usgs.gov Suggested citation: Ballachey, B.E., Monson, D.H., Esslinger, G.G., Kloecker, K., Bodkin, J., Bowen, L., and Mile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 57 publications
1
6
0
Order By: Relevance
“…However, several studies on sea otter demographics indicated that by 2012, the WPWS sea otter population had returned to pre-spill conditions. While sea otter abundance at the scale of WPWS had demonstrated modest increases since 1993, areas most severely impacted by oil-related mortality did not return to pre-spill numbers until 2011 [8]. The numerical recovery of sea otters was supported by improved survival of sea otters after 2009, with a return to rates observed prior to the spill [4,8,55].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, several studies on sea otter demographics indicated that by 2012, the WPWS sea otter population had returned to pre-spill conditions. While sea otter abundance at the scale of WPWS had demonstrated modest increases since 1993, areas most severely impacted by oil-related mortality did not return to pre-spill numbers until 2011 [8]. The numerical recovery of sea otters was supported by improved survival of sea otters after 2009, with a return to rates observed prior to the spill [4,8,55].…”
Section: Discussionmentioning
confidence: 98%
“…The effects of the 1989 Exxon Valdez oil spill (EVOS) on nearshore marine vertebrates in Prince William Sound, Alaska, including the sea otter (Enhydra lutris), have continued for more than two decades [1][2][3][4][5][6][7][8][9]. A series of long-term studies demonstrated a lack of recovery of sea otters through at least 2009 [1,4,[6][7][8][9], based on reduced rates of survival and exposure to residual oil in western Prince William Sound (WPWS), although the importance of continuing exposure as a factor constraining sea otter recovery has been debated [10][11][12]. To evaluate population health and recovery of sea otters and other species potentially affected by the spill, the Exxon Valdez Oil Spill Trustee Council established physiologic (based on biomarkers indicating exposure to aromatic hydrocarbons) and demographic (based on a return to expected abundance or reproduction/survival rates) criteria.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, sea otter populations in both Washington and SE Alaska were established by re‐introduction in 1969 and 1970 (Jameson et al., ; Kenyon, ), and thus, our resource‐limited samples from these regions come from subpopulations that have only recently reached carrying capacity. Similarly, sea otters in western Prince William Sound are believed to have been at carrying capacity for several decades, although this population was depleted by the Exxon Valdez Oil Spill in 1989, and only recently has recovered to the point that resources are once again the primary limiting factor (Ballachey et al., ; Monson, Doak, Ballachey, & Bodkin, ; Monson, Doak, Ballachey, Johnson, & Bodkin, ).…”
Section: Discussionmentioning
confidence: 99%
“…have been at or near carrying capacity for many decades (Tinker et al, 2017). Conversely, sea otter populations in both Washington and SE Alaska were established by re-introduction in 1969 and 1970 (Jameson et al, 1982;Kenyon, 1969) (Ballachey et al, 2014;Monson, Doak, Ballachey, & Bodkin, 2011;Monson, Doak, Ballachey, Johnson, & Bodkin, 2000).…”
Section: Thyroid Hormonesmentioning
confidence: 99%
“…Although much of the literature on the impacts of oil spills on marine organisms has concerned macrofauna [5][6][7][8], the impact of spilled oil on plants is potentially quite serious because plants are important determinants of the physical stability and resilience of coastal marine ecosystems [3], and of course photosynthetic organisms are responsible for producing much of the organic carbon that provides biomass and energy for the heterotrophic community. Although macrophytes such as Spartina alterniflora and Juncus roemerianus account for much of the resilience of salt marshes to perturbations such as hurricane storm surges, carbon and sulfur stable isotope studies have shown that the organic carbon in primary consumers in the Great Sippewissett marsh in Massachusetts and the Sapelo Island marsh in Georgia are derived about equally from Spartina and phytoplankton [9,10].…”
Section: Introductionmentioning
confidence: 99%